Comparative analysis of the surface roughness of conventional resins and filling after immersion in mouthwashes - Juliana de Souza Silva Zica; Isabela Araújo Fernandes; Fernanda Barcellos Ameno Faria; Fernanda Cruz Ferreira; Nívea Aparecida Reis Albuquerque; José Flávio Batista Gabrich Giovannini; Lidiane Cristina Machado Costa (Universidade Estadual de Campinas, 2020)
Aim: Bulk Fill composite resins were released on the market in order to reduce the time in clinical sessions by using increments of up to 5.0 mm thickness. The aim of this study was to evaluate the effect of the rinsing solutions on the surface roughness of the conventional composite and Bulk fill composite resins. Methods: 40 specimens were prepared from a 4.0mm x 10.0mm teflon matrix and photoactivated for 20 seconds, with 20 specimens made of Filtek Bulk-Fill composite resin (3M ESPE) and 20 specimens made with Filtek™ Z350 XT composite resin (3M ESPE). Each group was subdivided into 2 subgroups: G1 (Filtek™ Z350 XT-3M ESPE-immersed in Colgate PlaxWhitening®); G2 (Filtek™ Z350 XT-3M ESPE-immersed in PlaxFreshMint®); G3 (Filtek™ Bulk-Fill-3M ESPE-immersed in Colgate PlaxWhitening®) and G4 (Filtek™ Bulk-Fill-3M ESPE-immersed in Colgate PlaxFreshMint®). The surface roughness test was performed initially and after immersion in rinses by the Time Group Inc.-TR200® rugosimeter apparatus and the data were submitted to statistical analysis (two-way repeated measures ANOVA). Results: Surface roughness values of the Filtek™ Bulk-Fill composite resin (3M ESPE) were significantly higher than the Filtek™ Z350 XT composite resin (3M ESPE) (P <0.0001). However, no differences were identified before and after immersion in rinses with or without alcohol. Conclusion: The use of mouthwashes does not interfere with the surface roughness of the tested resins, but the composite resin Filtek Z350 XT (3M ESPE) presents a surface with less roughness.